IMPLEMENTATION OF POLICY ON BPJS HEALTH SERVICES: A PRELIMINARY QUALITATIVE STUDY IN OUTPATIENT UNIT OF THE GENERAL HOSPITAL OF ANUTAPURA, PALU - Napirah, Muhammad Ryman; Salmawati, Lusia; Rivai, Dian Rahmayanti (YCAB Publisher & IAKMI SULTRA, 2017)
Backgound: BPJS Health is a National health insurance to to administer health care benefits for all Indonesian people. Understanding the implementation of the policy on BPJS health is necessary.Objective: This study aims to explore the implementation of BPJS health policy in the outpatient unit of the general hospital of Anutapura Palu.Methods: This was a preliminary qualitative study. The informants consisted of Director of Hospital Services, Clinical nurses, BPJS staffs, and BPJS patients. Content analysis was used to analyze the data. Data were collected between March and April 2015Results: Findings of this study were described in several themes, namely no local regulation on BPJS implementation, lack of communication, inadequate human resource, good disposition, and good bureucracy structure.Conclusion: There were strengths and weaknesses in the implementation of Policy on BPJS health. It is suggested that the General Hospital of Anutapura Palu needs to propose the local regulation on BPJS, manage and facilitate good communication, and develop human resource management strategy.